2018
DOI: 10.1021/acsmacrolett.8b00485
|View full text |Cite
|
Sign up to set email alerts
|

Highly Anisotropic Glassy Polystyrenes Are Flexible

Abstract: We show that stretching polystyrene melts at a rate faster than the inverse Rouse time followed by rapid quenching below the glass transition temperature, results in a material that is flexible and remains so for at least six months. Oriented micro/nano fibers are observed in the flexible samples after the mechanical tests. The fibers are probably related to the highly aligned molecules in melt stretching. At room temperature, a tensile strength over 300MPa has been achieved for the flexible polystyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…In respect of glassy polymers, it has been found that the tensile strength is also influenced by the alignment of the polymer chains during processing. 2,3 In a recent paper by Huang et al, 3 it has been observed that for polystyrene, the larger stress in the melt stretching gives the larger tensile strength in the solid state, while the largest stress in the melt stretching is limited by fracture of the polymer liquid during stretching. This observation indicates that there is a connection between liquid fracture and solid fracture for polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In respect of glassy polymers, it has been found that the tensile strength is also influenced by the alignment of the polymer chains during processing. 2,3 In a recent paper by Huang et al, 3 it has been observed that for polystyrene, the larger stress in the melt stretching gives the larger tensile strength in the solid state, while the largest stress in the melt stretching is limited by fracture of the polymer liquid during stretching. This observation indicates that there is a connection between liquid fracture and solid fracture for polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, it can be seen from Table 1 that for intrinsically brittle polymers like PS and PMMA, the most outstanding improvement of mechanical behavior by pre‐stretching is their ductility, [ 46,48,49 ] some of which are even comparable to the traditional ductile amorphous polymers like polycarbonate. [ 50 ] One should distinguish this brittle‐to‐ductile transition from the increase of stretchability of brittle polymers with greater drawing temperature.…”
Section: Non‐crystallizable Polymersmentioning
confidence: 99%
“…Figure depicts a highly flexible aPS achieved by pre‐stretching at a rate above 1/Rouse time followed by a rapid quenching process. [ 48 ] Also, the enhanced mechanical properties can last for at least six months. As discussed previously, a precise control of competition between chain relaxation and chain stretching would determine the final properties of material.…”
Section: Non‐crystallizable Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the previous observation that PS became flexible when stretched faster than the inverse Rouse time during processing. 2 In addition, strain softening are observed in both samples, while the yield stress increases with the hydrogen bonding content.…”
mentioning
confidence: 92%